Crenças e quebranças de um corpo que dança: poéticas do benzimento na criação cênica - Rodrigues, Bianca Bazzo (2013)
This work is a discussion of the artistic process of an artist-researcher made from field research with benzedeiras and benzedores the state of Rio Grande do Norte. This is an investigation on the cultural universe of the popular benzeção as poetic element to the artistic dance. To discuss the different stages of the research and the relationships between the artist-researcher, the benzedeiras/benzedores and the creation/composition scenic, the work takes as reference the triangular relationship created by anthropologist Claude Lévi-Strauss, in his discussion on the effectiveness of symbols of healing, adapted to the context of benzeção . For dialogue between tradition, popular knowledge, scientific and artistic knowledge this work approaches as analytical reference the epistemological model of the type rhizome proposed by Deleuze and Guattari, understanding it as a model that seeks to form a network of relations in different paths of research, to establish connections between elements without target them or subordinating them. In the universe of benzeção , benzedeiras and benzedores carry a symbolic power that issued in whispered prayers, in peculiar gestures that form crosses in space, heal those who seek your prayers and blessing. In this research, the mixture of popular knowledge, artistic and academic knowledge, born an artistic work in the context of Performing Arts, more specifically dance, and between branches, saints, candles and conversations the work allowed other looks poetic for our popular culture, (re)asserting their cultural and human values through the art